PENERAPAN MODEL THE OPEN GROUP ARCHITECTURAL FRAMEWORK (TOGAF) UNTUK PERANCANGAN ARSITEKTUR ENTERPRISE (STUDI KASUS STMIK WIDYA PRATAMA PEKALONGAN) - Christian Yulianto Rusli; Risqiati Risqiati; Prastuti Sulistyorini (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The Open Group Architecture Framework (TOGAF) is a framework for enterprise architecture to analyze business architecture as a whole. TOGAF ADM explains how to find an organizational architecture in detail according to the needs of the business. Alignment of the application of information systems to organizational needs is an urgent need for STMIK Widya Pratama Pekalongan. The alignment of the application of this information system is only able to be answered by paying attention to the integration factors in the development of information systems.Information system integration aims to reduce the gap that occurs in theinformation system development process. This gap can be reduced by designing enterprise architecture. This study aims to design an enterprise architecture (blueprint) which includes business architecture, application architecture, data architecture and technology architecture, to support the business activities of STMIK Widya Pratama Pekalongan by using TOGAF ADM with 4 phase restrictions. The results of the study can contribute to stakeholders in STMIK Widya Pratama Pekalongan in planning the information system architecture to manage universities in accordance with the vision and mission set. Keywords: Enterprise Architecture, TOGAF Method.